Effects of biochar application on phytoremediation of gold mine tailings by vetiver grass, Chrysopogon zizanioides (L.). - Wahab, Mohd Syafiq (2015)
A study on the effects of biochar application on phytoremediation of gold mine tailings by using Vetiver grass, Chrysopogon zizanioides was conducted at Glass House Unit 2, Universiti Putra Malaysia. The objective of this study is to determine the effect of biochar on phytoremediation of tailings, to determine the most effective rate of rice husk biochar to be used, and to determine the capability of Vetiver grass, C. zizanioides in absorbing heavy metals. The treatment used for this study was at different rates of biochar (0, 25, 50, 75, and 100 grams) to be mix with the tailings and topsoil of Munchong series as the media for planting both of the plants. The mass of tailings were kept constant at 20 grams while the topsoil at 200 grams. The experimental unit had been designed with four replications and planted for 60 days. Maintenances like watering and weeding were manually done. After 60 days, plants were taken out from the plant and cut according to two parts, root and shoot. Then, dry ashing process was done to the parts and the samples are tested by Inductively Coupled Plasma (ICP) optical emission spectrometry to determine the amount of heavy metals that had been extracted. From the results, C. zizanioides showed potential in surviving on contaminated tailings and in uptaking heavy metals. In addition, rice husk biochar also showed its ability in immobilization of heavy metals, making it unavailable for uptakes. Soil management strategies should focus on these two methods for soil phytoremediation. The data was analysed by using Analysis of Variance (ANOVA) in Statistical Analyses System (SAS 9.2).